2013
DOI: 10.7860/jcdr/2013/5217.3049
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Peak Expiratory Flow Rate with Various Factors in a Population of Healthy Women of the Malwa Region of Punjab, India

Abstract: Objective: The present study was undertaken to study the variations in the Peak Expiratory Flow Rate (PEFR) with various factors like age, height, weight, body surface area (BSA) and the Body Mass Index (BMI) in healthy women of the Malwa region of Punjab, India. Material and Methods:Three hundred healthy women who were aged 20-50 years were selected from the Malwa region of Punjab and their PEFRs were determined. The influences of age, height, weight, BSA and BMI on the PEFR were studied. The PEFR test was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 5 publications
3
15
1
4
Order By: Relevance
“…In the present study, we found that PEFR was decreased significantly in both cigarette and cigar smokers compared to non-smokers, and our findings are in agreement with the findings of others [18][19][20][21][22]. One possible reason for the decrease in PEFR could be inflammation which is common and constant pathological finding in cigarette smokers [7].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study, we found that PEFR was decreased significantly in both cigarette and cigar smokers compared to non-smokers, and our findings are in agreement with the findings of others [18][19][20][21][22]. One possible reason for the decrease in PEFR could be inflammation which is common and constant pathological finding in cigarette smokers [7].…”
Section: Discussionsupporting
confidence: 83%
“…Others have reported that smoking affects both small and large airways [16,17]. Several studies have reported that PEFR was significantly lower in smokers than in non-smokers [18][19][20][21][22] and some studies found maximum reduction in PEFR was in bidi smokers than cigarette smokers [21]. High prevalence for both cigarette and cigar smoking in Andhra Pradesh, inconsistent…”
Section: Introductionmentioning
confidence: 99%
“…18,19 The correlation of height and weight with summer and winter PEFR value among rural and urban children was found to be highly significant(p value <0.001) as supported by studies by Składanowski, Kaur Harpreet and Manjunath [showed significant linear correlation of PEFR with height in boys (p<0.001, r=0.7624) and in girls (p<0.001, r=0.8825)]. 2,13,21 However, no correlation was found by Manjunath CB et al, between the PEFR values and the age.…”
Section: Discussionmentioning
confidence: 71%
“…PEFR was selected because it is widely accepted as a reliable parameter of pulmonary functions and is simple to perform as a bed-side test. Hadorn introduced PEFR in 1942 and it was accepted as a parameter of pulmonary function test (PFT) in 1949 [18,19,20]. The truncal fat may compress the thoracic cavity and restrict the diaphragmatic movement resulting in reduced vertical diameter of the thoracic cavity [21].…”
Section: Introductionmentioning
confidence: 99%